2020
DOI: 10.1128/aem.02904-19
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Cyanobacterium Synechococcus elongatus PCC 7942 Adapts to an Environment with Salt Stress via Ion-Induced Enzymatic Balance of Compatible Solutes

Abstract: Salinity is one of the most important abiotic factors in various natural habitats of microbes. Cyanobacteria are the most widely distributed family of photosynthetic microorganisms in environments with fluctuating salinity. In response to salt stress, many cyanobacteria de novo synthesize compatible solutes to maintain osmotic balance in the cell. However, the regulation of intracellular accumulation of these compounds is still not well understood. The freshwater cyanobacterium Synechococcus elongatus PCC 7942… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 57 publications
(103 reference statements)
0
33
0
Order By: Relevance
“…7 ). Sucrose serves as one of the major compatible solutes among cyanobacteria in freshwater habitats, and the intracellular accumulation of sucrose helps cyanobacteria cope with salt stress ( 76 78 ). Missing genes related to sucrose synthesis suggest that toxic strains may be less tolerant to salt stress, possibly due to expendable gene loss, as they exclusively inhabit freshwater environments ( 12 ) and thus encounter minimum fluctuations in salinity.…”
Section: Resultsmentioning
confidence: 99%
“…7 ). Sucrose serves as one of the major compatible solutes among cyanobacteria in freshwater habitats, and the intracellular accumulation of sucrose helps cyanobacteria cope with salt stress ( 76 78 ). Missing genes related to sucrose synthesis suggest that toxic strains may be less tolerant to salt stress, possibly due to expendable gene loss, as they exclusively inhabit freshwater environments ( 12 ) and thus encounter minimum fluctuations in salinity.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the effects of theophylline-induced glgP expression on glycogen storage and sucrose synthesis in XC14 facing salt stress, we supposed that this strategy might more possibly be valuable in non-hypersaline conditions to link the glycogen degradation metabolism and synthesis of desired metabolites. As for PCC 7942, sucrose synthesis would be activated through salt ion-induced activation of sucrose phosphate synthase and inhibition of invertase (Liang et al, 2020), while it has been confirmed that Sps from PCC 6803 (hereafter termed as Sps 6803 for short) was not a salt-activated enzyme, and introduction of the Sps 6803 in the another Synechococcus strain UTEX 2973 successfully resulted in a secretory synthesis of sucrose without the need for salt stress induction (Lin et al, 2020). We took the same strategy to construct a PCC 7942-derived cell factory producing sucrose under non-hypersaline conditions by overexpressing Sps 6803 in the FL92 strain which was previously FIGURE 5 | Effects of theophylline-induced glgP overexpression on salt-induced sucrose synthesis and secretion in PCC 7942 cell factories.…”
Section: Glgp Overexpression Improved Sucrose Synthesis In Pcc 7942-d...mentioning
confidence: 99%
“…It is triggered by the natural reaction of S7942 to osmotic changes due to salinization of the environment via increased sucrose levels in the cytoplasm, regulating the inner-cell turgor pressure (Vayenos et al 2020). Worth mention is that S7942 is able to tolerate maximally salinity of approximately 0.5 M NaCl (Ladas & Papageorgiou 2000;Du et al 2013), a salinity (2.9%) lower than that of seawater (3.5%) (Liang et al 2020). The high tolerance of S7942 in relative saline conditions and the increase of its sucrose levels renders this specific strain an excellent candidate towards eco-friendly and resource/energy recovering treatment of industrial wastewaters.…”
Section: Cultures In Btwwmentioning
confidence: 99%